Kajian Ilmu Falak dan Astronomi Dalam Sudut Pandang Filsafat Ilmu - Lauhatun Nashiha; Mahsun Mahsun (Astroislamica: Journal of Islamic Astronomy, 2024)
At first Ilmu Falak was no different from Astronomy. The study of astronomy is as broad as astronomy. However, over time there has been a narrowing of studies in Ilmu Falak. Why is that? Does that make it different from astronomy? This paper will discuss this using a philosophical approach. Data were obtained from various literatures which were then analyzed. This research attempts to study astronomy from a philosophical point of view